A comparative study of crisis consultancies between Singapore and Denmark: Distant cousins of the same destiny? - Pang, Augustine (Institutional Knowledge at Singapore Management University, 2013)
The aim of this article is to compare the state of crisis consultancies in Singapore and Denmark. Adapting and integrating indicators to assess professionalism, the study seeks to examine: 1) the level of expertise of public relations consultants in offering crisis management and communication consultancy to private and public organizations; 2) the level of experience of the consultants; and, 3) the value and expedience of the consultancy services offered to the clients. The research design comprised two stages. First, archival search of the websites of the public relations agencies that professed to offer crisis consultancy in the two countries was conducted. Second, the agencies that claimed to offer such services were contacted and a series of qualitative in-depth interviews with senior executives was conducted. The findings identified important differences and similarities between crisis consultancies in Singapore and Denmark.